Analog of the John theorem for weighted spherical means on a sphere - Volchkov, V. V.; Savost’yanova, I. M. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study generalizations of the class of functions with zero integrals over the balls of fixed radius. An analog of the John uniqueness theorem is obtained for weighted spherical means on a sphere.